INITIAL-STAGES OF THE THERMAL NITRIDATION OF THE SI(100) SURFACE WITH NH3 AND NO - A SURFACE SENSITIVE STUDY OF SI 2P CORE-LEVEL SHIFTS - Fauster, Thomas; et al. (Surface Science, 1994)
During thermal nitridation of the Si(100) surface, nitride regions grow laterally on the surface. Already at small coverages they have nearly the thickness which is found for the closed him. This thickness depends on the annealing temperature and is 10 Angstrom for 800 K and 15 Angstrom for 1200 K. The coordination of the silicon atoms with nitrogen atoms is determined by the heating temperature. At 800 K only a small fraction of the silicon atoms in the nitride is bound to four nitrogen atoms, whereas for 1200 K the majority of the silicon atoms is found in this environment, which is characteristic for stoichiometric silicon nitride. For 1200 K, growth mode, thickness, and chemical composition are independent of the nitrogen containing gases. For the stoichiometric closed nitride film we measured the edges of the band gap and the position of the Fermi level therein. Defect-induced unoccupied states could be detected within the band gap.